Ultrafast Response and Programmable Locomotion of Liquid/Vapor/Light-Driven Soft Multifunctional Actuators - Wang, Miao; Zhou, Lei; Deng, Wenyan; Hou, Yaqi; He, Wen; Yu, Lejian; Sun, Hao; Ren, Lei; Hou, Xu (ACS nano, 2022)
External-stimuli-driven soft actuators overcome several limitations inherent in traditional mechanical-driven technology considering the coming age of flexible robots, which might face harsh working conditions and rigorous multifunctional requirements. However, how to achieve multi-external-stimuli response, fast speed, and precise control of the position and angle of the actuator, especially working in a toxic liquid or vapor environment, still requires long-term efforts. Here, we report a multi-external-stimuli-driven sandwich actuator with aligned carbon nanotubes as the constructive subject, which can respond to various types of liquids (organic solvents), vapor, and solar light. The actuator has an ultrafast response speed (<10 ms) and can accurately adjust the bending angle range from 0° to 180°. Through manipulating the stimuli positions, actuators can be wound into varied turns when simulating a flexible robotic arm. Hence, liquid/vapor/light-driven actuators are able to support diverse programmable motions, such as periodic blooming, gesture variations, caterpillar crawling, toxic surface evading, and bionic phototaxis. We believe that this multifunctional actuator is promising in supporting a complex scenario to complete a variety of tasks in the fields of healthcare, bioengineering, chip technology, and mobile sensors.